Measuring the Essence of the Special Education Program in the Field of Religion: Realizing Religious Moderation in the Community - Syafaruddin, Baso (ETDC: Indonesian Journal of Research and Educational Review, 2023)
This article discusses Measuring the Essence of Special Education Programs in the Field of Religion in Realizing Religious Moderation in Society. The purpose of this paper is to measure the essence of Islamic religious education institutions in the midst of society in realizing religious moderation. This paper uses qualitative research methods in collecting, processing, and analyzing data related to this paper. In the discussion section, it is stated that special education programs in the field of religion as an effort to realize religious moderation in society are one option that can be taken. So that it requires government involvement in drafting regulations and Islamic religious education institutions as centers for fostering and studying studies on religious moderation that will be implemented in society. Therefore, the involvement of religious education institutions in realizing religious moderation in society has a very important role. Especially in preparing alumni who will become members of society to understand and practice Islamic religious values in society, Special education programs in the field of religion that are designed with curriculum, content standards, learning processes, and assessments adapted to the concept of religious moderation will be a breakthrough in realizing religious moderation in society. Because the alumni will provide guidance to the community about religious moderation.